Taphonomy of the Tianyuandong human skeleton and faunal remains. Issue 83 (June 2015) - Fernández-Jalvo, Yolanda; Andrews, Peter; Tong, HaoWen
Abstract: Tianyuan Cave is an Upper Palaeolithic site, 6 km from the core area of the Zhoukoudian Site Complex. Tianyuandong (or Tianyuan Cave) yielded one ancient (though not the earliest) fossil skeleton of Homo sapiens in China (42–39 ka cal BP). Together with the human skeleton, abundant animal remains were found, but no stone tools were recovered. The animal fossil remains are extremely fragmentary, in contrast to human skeletal elements that are, for the most part, complete. We undertook a taphonomic study to investigate the circumstances of preservation of the human skeleton in Tianyuan Cave, and in course of this we considered four hypotheses: funerary ritual, cannibalism, carnivore activity or natural death. Taphonomic results characterize the role of human action in the site and how these agents acted in the past. Because of disturbance of the human skeleton during its initial excavation, it is not known if it was in a grave cut or if there was any funerary ritual. No evidence was found for cannibalism or carnivore activity in relation to the human skeleton, suggesting natural death as the most reasonable possibility.